Gender and Scores in TOEFL-Like Inference-Type Listening Comprehension Tests - Dewi Mustika Ningrum; Lalu Jaswadi Putera; Arafiq Arafiq; Amrullah Amrullah (PALAPA, 2022)
This present study aims to identify, describe, and analyze the students’ gender and scores in answering inference-type questions of the TOEFL-like listening comprehension tests. It sought to find answers to two research questions: (1) What is the students’ ability in answering inference-type questions of the TOEFL-like listening comprehension tests based on gender; and (2) What are the percentages in answering the four types of inference questions i.e. functions, idiomatic language, contrary meaning, almost negative in the short dialogues part of the TOEFL-like listening comprehension test. Data were gathered from the TOEFL-like listening comprehension test results of 115 6th semester students of English Education Program. They were then analyzed using quantitative ex post facto method. 20 male and 20 female students were randomly chosen as the research samples which were grouped based on each gender. Data of the inference-type questions were taken from the short dialogues part of the Listening Comprehension section test. 5 inference-type questions were found in the test. The inference questions included 2 items about function of suggestion (Phillips, 2001:57), 1 item about idiomatic expressions (Phillips, 2001:70), 1 item about almost negative (Phillips, 2001:49), and 1 item about contrary meanings (Phillips, 2001:63). The results show that the mean score range of the male group 34.0 and the female group 36.0. Using Arikunto’s classification, the mean scores are converted into “Poor” category (30.6–50.5 points) which means both male and female groups share the same level of ability in answering inference-type questions of the TOEFL-like listening comprehension tests. In regards to the percentages of students answering the types of inference questions, both male and female gender groups scored poorly in all of them. In functions of suggestion type, only 32% female and 27.5% male students could answer this type of question, meaning that 67% of female and 73% of male students failed. In idiomatic language type, only 45% of male and 40% of female students managed to answer question of this type, meaning that 55%-60% of them did also fail. In almost negative type, only 40% of female and 35% of male students succeded, meaning that between 60%-65% of them did not succeed. In contrary meaning type, only 35% of both male and female students managed to score, meaning that 65% of them failed. This indicates that there is no gender gap or insignificant gap in the students’ ability in answering the inference-type questions of the TOEFL-like listening comprehension test based on gender. However, the results picture a worrying trend among university students since 53%-73% of male and female students show poor performance in answering inference questions in the TOEFL-like listening comprehension test. Thus, this study suggests that students regardless of their gender develop the ability and strategy in answering inference-type questions of the TOEFL-like listening comprehension test be it through self-directed or teacher-directed learnings.